Effect of the calcium binding protein TcCAL1 on the proliferation of Trypanosoma cruzi - Rodríguez Durán, Jessica Jenireth (2019)
Calcium homeostasis is implicated in essential processes of T. cruzilife cycle. Although several calcium binding proteins have beenidentified in T. cruzi genome, their role in Ca2+ signaling remain stillunknown. TcCAL1 is a hypothetical protein identified throughproteome analysis of T. cruzi, which has two EF-Hand domainsinvolved in Ca2+ binding. The hypothesis to be tested in this studywas that TcCAL1 overexpression could trigger alterations in theintracellular calcium homeostasis leading an effect on epimastigoteproliferation. For this purpose, the gene encoding tccal1 wasamplified by PCR and cloned fussed to a 6x histidine tag into thepTREX expression vector. The recombinant plasmidpTREX/tccal1x6His was used to transfect epimastigotes from T.cruzi Y or CL Brener strains. Selection of transgenic cultures wascarried out growing parasites in presence of increasingconcentrations of Geneticin. Overexpression of TcCAL1x6His fusionprotein was confirmed through western blot and affinitychromatography. Growth curves of recombinant cultures from Y orCL Brener strains were performed in triplicate, counting theparasites in a Neubauer chamber. Parasite cultures carrying theempty vector pTREX were used as controls. Data obtained wereprocessed using GraphPad Prism 6.0 Software and subjected tostatistical analysis by two-way ANOVA test. The preliminary resultsshowed that the overexpression of TcCAL1x6His affects the growthcurve of CL Brenner strain at the stationary phase but theproliferation Y strain is not affected. Additional experiments arebeing carrying out to validate these results and to study the effectof TcCAL1 overexpression on T. cruzi differentiation. Future assaysincluding parasites carrying the tccal1 gene silenced will contributeto validate our hypothesis and to reveal the function of TcCAL1 incalcium homeostasis of T. cruzi.